Biventricular pacing in heart failure: update on results from clinical trials - Haywood, Guy (BioMed Central, 2001)
Biventricular pacing or resynchronisation therapy is a non-pharmacological therapy for patients with chronic heart failure. Since being originally described in 1994, biventricular pacing has become a subject of intense interest and investigation. This review analyses the results reported in observational series and randomised trials, and seeks to answer two questions. If it works, why does it work? Which heart failure patients will it benefit?